INTERNALIZATION OF ‘KUALAT’ TEACHING AS AN ATTEMPT TO PREVENT CORRUPT BEHAVIOR AMONG CIVIL SERVANTS - Afnan Fuadi (Asia Pacific Fraud Journal, 2018)
Corruption in Indonesia has been increasingly rampant, ranging from high-ranking state officials to lower-level civil servants. The strategic tasks mandated to civil servants have in fact provided opportunities for them to commit corruption. Based on data from Indonesian Corruption Watch (ICW), from 2013 to 2016, most corruptors work as civil servants. Based on this fact, there seems to be an alternative approach that should be more optimized, namely a cultural approach. Indonesia has many unique teachings, one of which is the Javanese philosophy of life (Javanese Wisdom). This study deals with the kualat teaching derived from the Javanese Wisdom as an attempt to prevent corruption among civil servants. This study tries to explain the noble advice in the Javanese society, particularly about kualat teaching. The researcher conducted a survey to Civil Servants to find out whether the kualat teaching still existed in the minds of civil servants. Finally, the researcher offers the idea of the need for internalization of the kualat teaching in the material content of Leadership Education and Training (Diklatpim) IV. The researcher seeks to actively participate in preventing corruption among civil servants.